The theory and practice of irregular warfare warrior-scholarship in counter-insurgency - Mumford, Andrew; Reis, Bruno C. 1973- (Studies in insurgency, counterinsurgency and national security)
This book offers an analysis of key individuals who have contributed to both the theory and the practice of counterinsurgency (COIN).